WRKY9 transcription factor regulates cytochrome P450 genes CYP94B3 and CYP86B1, leading to increased root suberin and salt tolerance in Arabidopsis - Krishnamurthy, Pannaga; Vishal, Bhushan; Bhal, Amrit; Kumar, Prakash P. (Physiologia plantarum, 2021)
Salinity affects crop productivity worldwide and mangroves growing under high salinity exhibit adaptations such as enhanced root apoplastic barrier to survive under such conditions. We have identified two cytochrome P450 family genes, AoCYP94B3 and AoCYP86B1 from the mangrove tree Avicennia officinalis and characterized them using atcyp94b3 and atcyp86b1, which are mutants of their putative Arabidopsis orthologs and the corresponding complemented lines with A. officinalis genes. CYP94B3 and CYP86B1 transcripts were induced upon salt treatment in the roots of both A. officinalis and Arabidopsis. Both AoCYP94B3 and AoCYP86B1 were localized to the endoplasmic reticulum. Heterologous expression of 35S::AoCYP94B3 and 35S::AoCYP86B1 in their respective Arabidopsis mutants (atcyp94b3 and atcyp86b1) increased the salt tolerance of the transgenic seedlings by reducing the amount of Na+ accumulation in the shoots. Moreover, the reduced root suberin phenotype of atcyp94b3 was rescued in the 35S::AoCYP94B3;atcyp94b3 transgenic Arabidopsis seedlings. Gas‐chromatography and mass spectrometry analyses showed that the amount of suberin monomers (C‐16 ω‐hydroxy acids, C‐16 α, ω‐dicarboxylic acids and C‐20 eicosanol) were increased in the roots of 35S::AoCYP94B3;atcyp94b3 Arabidopsis seedlings. Using chromatin immunoprecipitation and electrophoretic mobility shift assays, we identified AtWRKY9 as the upstream regulator of AtCYP94B3 and AtCYP86B1 in Arabidopsis. In addition, atwrky9 showed suppressed expression of AtCYP94B3 and AtCYP86B1 transcripts, and reduced suberin in the roots. These results show that AtWRKY9 controls suberin deposition by regulating AtCYP94B3 and AtCYP86B1, leading to salt tolerance. Our data can be used for generating salt‐tolerant crop plants in the future.